PENINGKATAN KECERDASAN NATURALIS MELALUI KOLASE BAHAN ALAM PADA ANAK KELOMPOK A TK KEMALA BHAYANGKARI 54 NGAWI - Elisa Novie Azizah (JCE (Journal of Childhood Education), 2021)
Abstract This study aims to: 1) describe how collage of natural materials can improve the naturalist intelligence of group A children at TK Kemala Bhayangkari 54 Ngawi. 2) knowing the problems in the naturalist intelligence of group A children at TK Kemala Bhayangkari 54 Ngawi. The ressearch used is a type of classroom action research (PTK). The subjects of this study were children of group A TK Kemala Bhayangkari 54 Ngawi, with a total of 16 students. Data collection methods used in this study are observation and documentation. This research was conducted using 2 cycles, each cycle consisting of 4 stages, namely: planning, action, observation and reflection. The research was conducted by using collage activities using natural media in the form of leaves, seeds, nuts, and sand to improve children's naturalist intelligence. Furthermore, in the pre-action the percentage increase in children's naturalist intelligence 25% was in the criteria of starting to develop (MB), in the first cycle it increased to 56% in the criteria of developing as expected (BSH) and in the second cycle it increased again to 75% in the very developing criteria. good (BSB). Based on the results of the study, the authors conclude that the collage of natural materials can increase naturalist intelligence in group A children at TK Kemala Bhayangkari 54 Ngawi.